2014
DOI: 10.1002/jtr.2009
|View full text |Cite
|
Sign up to set email alerts
|

Mix between Satisfaction and Attributes Destination Choice: A Segmentation Criterion to Understand the Ski Resorts Consumers

Abstract: This study examined the attributes prioritized by tourists when choosing a winter sports destination and their degree of satisfaction with the services provided by Portugal's only ski resort. Two hundred tourists completed a questionnaire with factor analysis then deployed to extract the data that served as the basis for cluster analysis. Our results report discrepancies between the attributes valued by tourists when choosing winter sports destinations and their degree of satisfaction with the ski resort's ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 76 publications
1
14
0
Order By: Relevance
“…These results, however, showed an opposite trend when compared with results obtained by Matzler et al [50], concluding that the quality of slopes was considered as an important factor for male tourists, and services associated with the quality of restaurants were considered more satisfactory to female tourists. Although this study's results did not indicate significant differences when compared with respect to gender, several studies have found differences in consumer profile between men and women [41,43]. This approach, was also mentioned in other studies conducted in other sports contexts, concluding that the motivation and expectation regarding dimensions of service quality, may dependent of gender variable [27,54].…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…These results, however, showed an opposite trend when compared with results obtained by Matzler et al [50], concluding that the quality of slopes was considered as an important factor for male tourists, and services associated with the quality of restaurants were considered more satisfactory to female tourists. Although this study's results did not indicate significant differences when compared with respect to gender, several studies have found differences in consumer profile between men and women [41,43]. This approach, was also mentioned in other studies conducted in other sports contexts, concluding that the motivation and expectation regarding dimensions of service quality, may dependent of gender variable [27,54].…”
Section: Discussionsupporting
confidence: 54%
“…Not having that kind of experience can affect appreciation of services, since there is no reference to compare [41]. The results in Table 3 show that cluster 4 is composed by 54.9 % of consumers who had never attended another ski resort, corresponding precisely to tourists/visitors satisfied with everything.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Identifying factors that influence satisfaction is fundamental to keep the consumers [15]. It is done to find out what makes the customer buy again, so that in the long run it is a strategy that must be done.…”
Section: Defining Re-visit Intentionmentioning
confidence: 99%